Chalcogenides Preparation and Applications - Vikraman, Dhanasekaran (IntechOpen, 2022)
Chalcogenides are chemical compounds that contain one or more sulfides, selenides, and tellurides (S, Se, Te) paired with an electropositive counterpart. They are developed through a strong covalent bond creating a variety of morphological structures, frequently organized by hexagonal or monoclinic geometry. The derivatives of chalcogenide materials such as binary, ternary, and quaternary are pertinent in various applications, including sensors, batteries, opto-electronics, photovoltaics, fuel cells, and photocatalysts. Chalcogenide-based materials can be developed through a variety of physical and chemical methodologies. This book provides a general overview of these methodologies and discusses the various chalcogen materials and their different applications. It includes eight chapters in three sections: "Chalcogen Fabrication", "Solar Cells and Batteries" and "Nanoscale Devices".